Study of the conceptual metaphors in Persian proverbs - محمد رضایی; نرجس مقیمی (مطالعات زبانی و بلاغی)
The theory of the conceptual metaphor is related to the cognitive, linguistic which studies the manner of the conception and the cognition in the human mind. Based on this theory, metaphors are not lingual function in the service of the being literary of the context, but the fundamental instrument for conceptualizing the abstract and intangible matters. The circle of their influence and function is not vocabulary, but the concept and meaning.